The sources and seasonal variations of the chemical components in the deposition samples in Kirklareli, Turkey - AKKOYUNLU, BÜLENT OKTAY (My University, 2022)
This study was carried out in the central district of Kirklareli province in Turkey. It presents the chemical composition of three deposition types, namely wet, bulk and dry. In this study, 150 deposition samples (wet + bulk + dry) were collected for a year in the urban and suburban areas in the central district of Kirklareli. The concentrations of the main cations (Ca2+, K+, Na+, Mg2+, NH4+) and main anions (SO42-, Cl-, NO3-) in the collected deposition samples were determined. The seasonal variations of the concentrations of the major ions in the three deposition types were studied. The wet and dry deposition fluxes of major ions were calculated. Among the major ions, the ion with the highest annual mean flux values in the wet deposition is Ca2+ in the urban area, while it is Cl- in the suburban area. In the wet deposition, the annual mean flux values of Ca2+ in the urban area and Cl- in the suburban area were 65.40 and 38.09 mg m(-2) h(-1), respectively. The relationship between ion concentrations and acid deposition was also investigated and the sources of ions were determined. The arithmetic mean pH values of the samples in the urban and suburban areas were 6.39 and 6.14 in wet deposition, 6.75 and 6.41 in bulk deposition, and 7.36 and 6.56 in dry deposition, respectively. The backward trajectories arriving at the region during the study period were divided into two groups. In the first cyclone group, SO42- was to 97 % of anthropogenic origin in both the urban and suburban areas.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences; ion concentration; deposition flux; trajectory analysis; enrichment factor; WET PRECIPITATION; THESSALONIKI